The Effectiveness Of The Family Hope Program (PKH) In Reducing Poverty Rates In Tanjung Selamat Village, Medan Tuntungan District - Saripah Saripah; Rahmad Sembiring; Uswatun Hasanah (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to analyze the effectiveness of the Family Hope Program (PKH) in reducing poverty rates in Tanjung Selamat Village, Medan Tuntungan District, where structural poverty remains a major challenge despite a downward trend from 9.41% (2015) to 7.94% (2024). This study uses a quantitative approach applied to time-series data from 2016 - 2025 with secondary data from BPS and PKH officers in Tanjung Selamat Village which are analyzed using Multiple Linear Regression techniques after fulfilling classical assumption tests such as normality, multicollinearity and heteroscedasticity. The results of this study's analysis indicate that the Number of PKH Assistance Recipients (X1) has a positive and significant partial effect on reducing the Percentage of Poor Population (Y) with a calculated t-value of 1.95 > t-table of 1.89 (sig. 0.04 < 0.05). The value of PKH Assistance (X2) also has a positive and significant partial effect with a t-count of 1.929 > t-table of 1.89 (sig. 0.02 < 0.05). Simultaneously, both variables show an F-count of 4.855 > F-table of 4.74 (sig. 0.04 < 0.05) with a coefficient of determination of 89.5% which explains variations in poverty, the rest is influenced by external factors of 10.5%